2018
DOI: 10.1186/s13287-018-0883-4
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency electromagnetic fields promote mesenchymal stem cell migration by increasing intracellular Ca2+ and activating the FAK/Rho GTPases signaling pathways in vitro

Abstract: BackgroundThe ability of mesenchymal stem cells (MSCs) to migrate to the desired tissues or lesions is crucial for stem cell-based regenerative medicine and tissue engineering. Optimal therapeutics for promoting MSC migration are expected to become an effective means for tissue regeneration. Electromagnetic fields (EMF), as a noninvasive therapy, can cause a lot of biological changes in MSCs. However, whether EMF can promote MSC migration has not yet been reported.MethodsWe evaluated the effects of EMF on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Overexpression of KiSS-1 reduces the invasiveness of colorectal cancer cells by blocking the PI3K/AKT/NF-κB pathway and inhibiting the expression of MMP-9 protein [37]. Studies have shown that RhoA signaling and the PI3K/AKT pathway mediate cancer cell invasion [38,39], and the FAK-RhoA pathway may influence cancer cell motility [40,41]. According to our results, sinulariolide inhibited the FAK/PI3K/AKT/mTOR pathway and reduced the MMP-2/-9 and uPA protein expressions, preventing invasion and migration of AGS and NCI-N87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of KiSS-1 reduces the invasiveness of colorectal cancer cells by blocking the PI3K/AKT/NF-κB pathway and inhibiting the expression of MMP-9 protein [37]. Studies have shown that RhoA signaling and the PI3K/AKT pathway mediate cancer cell invasion [38,39], and the FAK-RhoA pathway may influence cancer cell motility [40,41]. According to our results, sinulariolide inhibited the FAK/PI3K/AKT/mTOR pathway and reduced the MMP-2/-9 and uPA protein expressions, preventing invasion and migration of AGS and NCI-N87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among several possible control elements of cytophysical properties, the Rho family of GTPases and downstream signals appear to play the most prominent role in modulating the biochemical pathways of cell migration 21 - 23 . Although [Ca 2+ ] i is known to be a prominent regulator that can exert multiple effects on the structure and dynamics of the actin cytoskeleton 24 , 25 , whether [Cl - ] i is involved this response remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…PEMF stimulation has been previously shown by others to exert anti-inflammatory effects by activating adenosine receptors [41,44], while modulating intracellular calcium and activating the mechanotransduction FAK/Rho GTPases signaling pathways to induce MSC migration [67]. PEMF exposure was also shown to activate a calcium-mitochondrial axis stimulating mitochondrial respiration and promoting both mitochondriogenesis and myogenesis as well as reducing basal apoptosis and increasing telomere length via a process of adaptive magnetic mitohormesis [35].…”
Section: Discussionmentioning
confidence: 96%